A New Portrait of Constitutive Heterochromatin: Lessons from Drosophila melanogaster. - Marsano, R.M.; Giordano, E.; Messina, G.; Dimitri, P. (Trends in Genetics, 2019)
Constitutive heterochromatin represents a significant portion of eukaryotic genomes, but its functions still need to be elucidated. Even in the most updated genetics and molecular biology textbooks, constitutive heterochromatin is portrayed mainly as the 'silent' component of eukaryotic genomes. However, there may be more complexity to the relationship between heterochromatin and gene expression. In the fruit fly Drosophila melanogaster, a model for heterochromatin studies, about one-third of the genome is heterochromatic and is concentrated in the centric, pericentric, and telomeric regions of the chromosomes. Recent findings indicate that hundreds of D. melanogaster genes can 'live and work' properly within constitutive heterochromatin. The genomic size of these genes is generally larger than that of euchromatic genes and together they account for a significant fraction of the entire constitutive heterochromatin. Thus, this peculiar genome component in spite its ability to induce silencing, has in fact the means for being quite dynamic. A major scope of this review is to revisit the 'dogma of silent heterochromatin'.